Impact of Working Conditions and Supervision on Academic Staff's Job Satisfaction at Dilla University - Getachew Alene Chekol (International School for Social and Business Studies, 2019)
Organizations in the 21st century are faced with more challenges than ever before. Job satisfaction is assumed as a one of the main factors amongst academic staff and placed as a basic inner feeling for them. The researcher was inspired to carry out this research because different stakeholders often question why job satisfaction at Dilla University is low. The purpose of this study was to investigate the impact of working conditions and supervision on academic staff's job satisfaction at Dilla University. This study tries to identify the relationship between working conditions, supervision, and job satisfaction. A descriptive correlational research design was adopted for the study. Both questionnaires and interviews were used to collect the data. Stratified sampling techniques were used. Both quantitative and qualitative approaches were employed. The study found that there is a positive significant relationship between working conditions, supervision and job satisfaction. The study also revealed that the lack of equipment and tools for academic staff to carry out their tasks was one of the major challenges that academics experienced. The study recommends that top management should improve working conditions within the organization. The working conditions should be conducive to the academic staff's health and safety at the University. The decision makers at Dilla University need to pay more attention to the physical aspects of the working environment, such as buildings, equipment, furniture, lighting and air-conditioning.